Conceptualization, use, and outcomes associated with compassion in the care of youth with childhood-onset disabilities: a scoping review - Patsakos, Eleni M.; Patel, Stuti; Simpson, Robert; Nelson, Michelle L. A.; Penner, Melanie; Perrier, Laure; Bayley, Mark T.; Munce, Sarah E. P. (Frontiers in Psychology, 2024)
Introduction To examine the scope of existing literature on the conceptualization, use, and outcomes associated with compassion in the care of youth with childhood-onset disabilities. Methods A protocol was developed based on the Joanna Briggs Institute (JBI) scoping review method. MEDLINE, EMBASE, PsycINFO, Cochrane Central Register of Controlled Trials, and EBSCOhost CINAHL, were searched. Results Eight studies were selected for inclusion; four used quantitative methodology, and four used qualitative methods. Compassion was not defined a priori or a posteriori in any of the included studies. The concept of self-compassion was explicitly defined only for parents of youth with childhood-onset disabilities in three studies a priori. The most reported outcome measure was self-compassion in parents of youth with childhood-onset disabilities. Self-compassion among parents was associated with greater quality of life and resiliency and lower stress, depression, shame and guilt. Discussion There is limited evidence on the conceptualization, use, and outcomes associated with compassion among youth with childhood-onset disabilities. Self-compassion may be an effective internal coping process among parents of youth with childhood-onset disabilities. Further research is required to understand the meaning of compassion to youth with childhood-onset disabilities, their parents and caregivers. Systematic review registration https://doi.org/10.17605/OSF.IO/2GRB4.